2012
DOI: 10.1111/j.1600-0706.2011.20177.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of insects and ungulates on root growth in a native grassland

Abstract: Insects and ungulates co‐occur in grasslands, often feeding on the same plants at the same time and potentially having interactive effects on plant growth. Further, ungulate–insect interactions may differ between native ungulate guilds and domesticated cattle. Despite the prevalence of insects and ungulates in native grasslands, experiments simultaneously manipulating the densities of both these groups are rare. Using large, replicated paddocks, as well as insecticide application, we restricted access to veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…However, increased herbivory towards range limits and beyond reduced plant fitness more so than in their core range. It is not uncommon to find greater biomass in plant populations and communities with ungulate exclusion (Clark et al, 2012; Evans et al, 2015; Maron & Pearson, 2011), but increased growth of individuals planted below their range without mammals is a novel result. Additionally, low biomass at F .…”
Section: Discussionmentioning
confidence: 99%
“…However, increased herbivory towards range limits and beyond reduced plant fitness more so than in their core range. It is not uncommon to find greater biomass in plant populations and communities with ungulate exclusion (Clark et al, 2012; Evans et al, 2015; Maron & Pearson, 2011), but increased growth of individuals planted below their range without mammals is a novel result. Additionally, low biomass at F .…”
Section: Discussionmentioning
confidence: 99%
“…Where vegetation was grazed, we assigned that quadrat a value of one for that vegetation group, otherwise zero. Values assigned for each vegetation group were summed per transect and divided by 10 to obtain a frequency of grazing use ranging from 0% to 100% (Clark et al 2012).…”
Section: Diet Selection Of Large Herbivores and Grasshoppersmentioning
confidence: 99%
“…It is true that large mammals may alter foraging behavior in response to other ungulates (Bailey et al 1996), as well as disturbances from other fauna and their impacts on vegetation (e.g., prairies dogs; Davidson et al 2010), yet whether and how large herbivores alter foraging behavior in response to insect activity is still poorly understood (Clark et al 2012). We found that herbivorous insects did influence the foraging behavior of large herbivores: Sheep tended to spend more time on grazing during the peak of the growing season (August) when they grazed with grasshoppers ( Fig.…”
Section: The Positive Interactions Between Vertebrate and Invertebratmentioning
confidence: 99%
“…When a plant was removed, we assigned that bite a value of one for the belonging species group. Values assigned for each species group were summed per livestock type and divided by total bites of plants to obtain a relative grazing frequency of species groups ranging from 0%-100%, similar to procedures of Clark et al (2012) and Zhong et al (2014).…”
Section: Livestock Foraging Behavior Measurementmentioning
confidence: 99%